Successful project management : applying best practices and real-world techniques with Microsoft Project - Biafore, Bonnie (Business skills series (Redmond, Wash.), 2011)
Explains how to use the project management software to build a project schedule, work with a budget, manage project resources, communicate information, manage risk, and archive historical information.